Cerebrospinal fluid protein in Guillain–Barré syndrome: Need for age‐dependent interpretation. (30th November 2020) - Hegen, Harald; Ladstätter, Felix; Bsteh, Gabriel; Auer, Michael; Berek, Klaus; Di Pauli, Franziska; Walde, Janette; Wanschitz, Julia; Zinganell, Anne; Deisenhammer, Florian
Abstract: Background and purpose: Elevated cerebrospinal fluid (CSF) total protein in patients with acute ascending paresis is indicative of Guillain–Barré syndrome (GBS). Recent studies showed that the outdated, but still widely used upper reference limit (URL) for CSF total protein of 0.45 g/L leads to false‐positive results, mainly as a result of lack of age‐adjustment. The objective of this study was to assess the frequency of increased CSF total protein in adult GBS patients according to a new age‐dependent URL. Methods: Patients with GBS treated at the Medical University of Innsbruck between 2000 and 2018 were included in this study. Demographic, clinical, electrophysiological and CSF data were obtained from patients' medical charts. Frequency of increased CSF total protein depending on disease duration was compared using the conventional URL of 0.45 g/L and the age‐dependent URL. Results: Ninety‐seven patients with GBS aged 57 ± 18 years, comprising 38% women, underwent CSF sampling within a median of 6 days after symptom onset. The median CSF total protein concentration was 0.65 g/L and correlated with disease duration. Overall, 74% of patients had elevated CSF total protein levels using the conventional URL, as opposed to 52% applying the age‐dependent URL. At 0–3, 4–7, 8–14 and >14 days after disease onset, elevated CSF total protein was found in 46%, 84%, 78% and 100% of patients using the conventional URL, and in 32%, 53%, 65% and 64% of patients using the age‐dependent URL. In multivariate analysis, significant predictors of elevated CSF total protein were disease duration and the demyelinating GBS variant. Similar results were obtained for CSF/serum albumin quotient (Qalb ). Conclusion: Fewer true‐positives for CSF total protein and Qalb must be considered in suspected GBS, especially in the early disease course. Abstract : Cerebrospinal fluid (CSF) total protein and CSF/serum albumin quotient are less frequently elevated in patients with Guillain–Barré syndrome than previously reported, as a result of novel age‐dependent upper reference limits that reduce false‐positives and avoid over‐interpretation of slightly elevated protein levels in the elderly.